2018
DOI: 10.1155/2018/3190548
|View full text |Cite
|
Sign up to set email alerts
|

The Continental Divide: Anti-TNF Use in Pediatric IBD Is Different in North America Compared to Other Parts of the World

Abstract: Background and Aims Use of anti-TNF therapies varies internationally. As an initiative of the international Pediatric IBD Network (PIBDNet), we compared global pediatric IBD anti-TNF practice patterns. Methods Physicians were surveyed about anti-TNF use in Crohn's disease (CD) and ulcerative colitis (UC). Chi-squared, independent samples Mann–Whitney U, or related samples Wilcoxon signed rank tests were used to compare groups. Results 344 physicians treating pediatric IBD responded from 43 countries (54% North… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 27 publications
1
10
1
Order By: Relevance
“…The trough levels during induction were higher during 2016, and it is very likely that this reflects a change in clinical practice during this period, as studies carried out around this time reported better responses in young children with higher doses. 16,17 Disappointingly, although the trough levels during induction were higher, we did not observe any increase in the proportion of patients that maintained their therapeutic response. There were no major adverse events during the study period, no alarming signs and no acute infusion reactions with either of these drugs.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…The trough levels during induction were higher during 2016, and it is very likely that this reflects a change in clinical practice during this period, as studies carried out around this time reported better responses in young children with higher doses. 16,17 Disappointingly, although the trough levels during induction were higher, we did not observe any increase in the proportion of patients that maintained their therapeutic response. There were no major adverse events during the study period, no alarming signs and no acute infusion reactions with either of these drugs.…”
Section: Discussioncontrasting
confidence: 59%
“…During the first year of therapy, more than one‐third of the patients discontinued the therapy, although therapy optimisation was frequent. The trough levels during induction were higher during 2016, and it is very likely that this reflects a change in clinical practice during this period, as studies carried out around this time reported better responses in young children with higher doses . Disappointingly, although the trough levels during induction were higher, we did not observe any increase in the proportion of patients that maintained their therapeutic response.…”
Section: Discussionmentioning
confidence: 47%
“…There is a critical need for a real-world PK investigations as infliximab monotherapy is favored over combination therapy in pediatric IBD practices in North America with an alarming rate of subtherapeutic infliximab levels with as-labeled dosing. 6,17 Additionally, although the PK parameters are comparable to previously published PK models in CD, 11,18 our study has notable improvements in study design and model prediction. Specifically, we prospectively enrolled patients with CD across four medical centers and collected longitudinal blood samples to conduct a more thorough PK analysis for patients receiving infliximab monotherapy.…”
Section: Discussionsupporting
confidence: 58%
“…There is a critical need for a real‐world PK investigations as infliximab monotherapy is favored over combination therapy in pediatric IBD practices in North America with an alarming rate of subtherapeutic infliximab levels with as‐labeled dosing 6,17 . Additionally, although the PK parameters are comparable to previously published PK models in CD, 11,18 our study has notable improvements in study design and model prediction.…”
Section: Discussionmentioning
confidence: 77%
“…An increased risk for life‐threatening malignancies such as lymphoma has been also reportedly associated with thiopurine use in children with IBD 13 . Therefore, paediatric IBD specialists in North America prefer methotrexate over thiopurines for combination treatment with anti‐tumour necrosis factor agents 14 . However, there is currently a lack of evidence regarding the efficacy of methotrexate in the treatment of IBD 15,16 …”
Section: Introductionmentioning
confidence: 99%